The factors influencing agropreneurs’ intention using TPB: a study of fertigation programme in Selangor, Malaysia - Wan Azman, Wan Attieyyah Rahman; Mohammad Afandi, Syamsul Herman; Kamarulzaman, Nitty Hirawaty; Wana Ismail, Normaz (Universiti Teknologi PETRONAS, 2024)
Malaysia has been continuously practicing the fertigation system, which is applying fertiliser solutions with irrigation water, typically through a micro-sprinkler or a drip system. This system has helped numerous small and medium-scale agropreneurs (agriculture entrepreneur) develop constant business. At a larger scale, fertigation is a means to address food security issues. Many small and medium-scale agropreneurs apply fertigation techniques in their crop cultivation. What are the underlying factors that cause them to continue using these techniques in their cultivation practices? To what extent do their intentions in crop production using fertigation techniques measured? This study sought to investigate the factors that affect small and medium-scale agropreneurs’ intention to continue practicing fertigation techniques in their agricultural activities. Using the Theory of Planned Behavior (TPB), this study examined 319 small and medium-scale agropreneurs’ intentions and the moderating effect of personality traits under Farmer’s Organization Authority (FOA) agency. The results revealed that the interests of FOA participants were determined significantly by subjective norms and personality traits while attitude, perceived behavioral control did not affect their intentions. Household income, number of household, age and education similarly provides significant effect of the agropreneurs’ intention. The findings of this study lead to the success of the fertigation program conducted and can further maximise the application of this technique to the cultivation of diverse crops. Additionally, the framework used can be adapted in various agricultural subsectors such as crop production, animal production, fisheries and agribusiness.